Exploratory Study on the Importance of Counseling Guidance Services for Students at UMSIDA - Dwi Nastiti; Nur Habibah (Psikologia : Jurnal Psikologi, 2016)
This research conducted because of many college student have problems associated with their learning process, examples : learning achievement down, relation problems with their parent or friends, adaptation with new environment or rules, etc., but theres no right place, like guidance and counseling, that can help have the college student that have difficulty solving their problems at the college. There 4 (four) aims of this research are : (1) If guidance and counseling services needed, (2) Whether college student will take advantage of the guidance and counseling services, (3) What kind of guidance and counseling services they need, (4) What factors that make student college need guidance and counseling services.The variable of this research is the need of guidance and counseling services at the college. This variable means the need of psychological assistance from professionals who have the expertise and authority to give guidance and counseling servives to individu who are in college which aims to help solving problems so that the student develop optimally in accordance with their potential.The population of this research are 6.163 college student of Univesitas Muhammadiyah Sidoarjo 2014-2015. The sample taken with the technique non probability sampling taken using incidental sampling method. Determination of the number of samples based on the Issac Michael Table (with standart error of 1%) and representative samples obtained as 598 student, but samples collected 638 student.The analysis that used in this research is descriptive analysis with analysis of the percentage. The result show that 77,4% students think that the guidance and college services required at college, and 78,06% students will utilize the available guidance and counseling services. The form of services that most needed is Guidance and counseling services (19,2%), dan 18,37% student will utilize the services when they have a difficult problem solved.